2021
DOI: 10.3389/fmicb.2021.658772
|View full text |Cite
|
Sign up to set email alerts
|

The Dissemination and Molecular Characterization of Clonal Complex 361 (CC361) Methicillin-Resistant Staphylococcus aureus (MRSA) in Kuwait Hospitals

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) belonging to clonal complex 361 (CC361-MRSA) is rare among patients’ populations globally. However, CC361-MRSA has been isolated with an increasing trend among patients in Kuwait hospitals since 2010. This study investigated the molecular characteristics of CC361-MRSA isolated from patients in Kuwait hospitals in 2016–2018 to understand their genetic relatedness and virulence determinants. Of 5,223 MRSA isolates investigated by DNA microarray, 182 (3.4%) isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
6
1
Order By: Relevance
“…PVL genes were detected in 35.4% of the MRSA isolates, where the majority belonged to ST772-V and ST361-V. Although ST361 is a rare MRSA clone, it has recently expanded steadily in the Arabian Gulf region, demonstrating its ability to disseminate [107]. Meanwhile, most MRSAs that lacked PVL genes belonged to the classic Asian MRSA clone, ST239-III, which was multidrug-resistant.…”
Section: Myanmarmentioning
confidence: 99%
“…PVL genes were detected in 35.4% of the MRSA isolates, where the majority belonged to ST772-V and ST361-V. Although ST361 is a rare MRSA clone, it has recently expanded steadily in the Arabian Gulf region, demonstrating its ability to disseminate [107]. Meanwhile, most MRSAs that lacked PVL genes belonged to the classic Asian MRSA clone, ST239-III, which was multidrug-resistant.…”
Section: Myanmarmentioning
confidence: 99%
“…It often complicates influenza with a death toll significantly surpassing those of many past pandemics. S. aureus owes its pathogenicity to a series of necrotizing exotoxins that induce a marked neutrophil response resulting in suppurative tissue necrosis ( 4 7 ). Particularly potent is a strain of MRSA that secretes an exotoxin known as Panton–Valentine leucocidin (PVL) as well as complicating influenza, this strain has resulted in fatal septic shock in previously healthy persons ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…SCC mec genomic island comprises two site-specific recombinase genes namely ccrA and ccrB [cassette chromosome recombinase] accountable for mobility. Currently, SCC mec elements are classified into types I, II, III, IV and V based on the nature of the mec and ccr gene complexes and are further classified into subtypes according to variances in their J region DNA ( 5 7 ). SSC mec type IV has been found in community-acquired isolates with various genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, draft‐genome of ST672‐MRSA from clinical cases such as sepsis (Bakthavatchalam et al ., 2017), ocular infection (Velusamy et al ., 2014) and septicaemia (Khedkar et al ., 2012) has been reported previously from different parts of India. Further, large‐scale hospital surveillance in Kuwait revealed a high prevalence of ST361 and ST672 MRSA carrying immune evasion clusters (IEC) and staphylococcal enterotoxins (SEs) as virulence factors, and fusC , aphA3 and erm ( B ) /erm ( C ) loci, conferring resistance to fusidic acid, kanamycin and erythromycin respectively (Sarkhoo et al ., 2021). Another study again from the Kuwait hospitals reported the incidence of ST672‐MSSA with reduced susceptibility to chlorhexidine (Vali et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%